ATG-Fresenius increases the risk of red blood cell transfusion after kidney transplantation - Sebti, Maria; Petit-Hoang, Camille; Chami, Btissam; Audureau, Étienne; Cordonnier-Jourdin, Catherine; Paul, Muriel; Pourcine, Franck; Grimbert, Philippe; Ourghanlian, Clément; Matignon, Marie (Frontiers in Immunology, 2022)
In sensitized kidney allograft recipients, induction therapy of choice is anti-thymocyte globulins (ATG), including Thymoglobulin® (Thymo) and ATG-Fresenius (ATG-F). We conducted a three-year monocentric observational study to compare the impact of ATGs on haematological parameters. We included adult kidney transplant recipients treated with ATG induction therapy, either Thymo or ATG-F, on a one-in-two basis. Primary endpoint was red blood cell (RBC) transfusions within 14 days after transplantation. Among 309 kidney allograft recipients, 177 (57.2 %) received ATG induction, 90 (50.8 %) ATG-F and 87 (49.2%) Thymo. ATG-F group received significantly more RBC transfusions (63.3% vs. 46% p= 0.02), and of bigger volumes (p = 0.01). Platelet transfusion was similar in both groups. Within 14 and 30 days after transplantation, older age, ATG-F induction, and early surgical complication were independently associated with RBC transfusion. Patient survival rate was 95 % and death-censored kidney allograft survival rate was 91.5 % at 12 months post-transplantation. There was no difference in the incidence of acute rejection and infections or in the prevalence of anti HLA donor specific antibodies. In conclusion, after kidney transplantation, ATG-F is an independent risk factor for early RBC transfusion and early thrombocytopenia without clinical and biological consequences. These new data should be clinically considered.